Water content effect on biofilm formation and bio-corrosion process in biodiesel-diesel storage tank - Nur Ramadhani, Aida; Harimawan, Ardiyan; Devianto, Hary (International Journal of Engineering and Technology, 2018)
This study focused in the effect of water content on biofilm and bio-corrosion, and knowing its influence on biodiesel-diesel blends’ quality. Biodiesel is hygroscopic and less stable, makes this fuel needs more attention in storing. Fuel is usually stored in a storage tank of carbon steel which easily corroded by microorganisms, such as Bacillus megaterium. Corrosion occurs because microorganisms use fuel as nutrients and water content in hygroscopic biodiesel supports to grow and metabolize. Experiments were carried out by immersing carbon steel in medium 30% biodiesel (B30) for 21 days with water content variation of 0%, 5%, and 10% volume. The number of colonies in biofilms increased up to 1,3 times in a 10% water content. A uniform biofilm provides an inhibitory effect on corrosion per time, also layer of iron phosphate formed on water content variation, so the highest 0.642 ± 0.28 mm/year on 0% water content. Fe2O3, Fe3O4, and FeOOH are the corrosion product by Bacillus megaterium. The highest biodegradation efficiency achieved by variation water content both 5% and 10% were 68.5% and 67.23%, and then followed by no water content at 60.40%.
Keywords: Bacillus Magisterium; Bio Corrosion; Biodiesel; Biofilm; Degradation; Water Content.